Germany's Western Front. translations from the German official history of the Great War, 1914 - Humphries, Mark Osborne, 1981-; Maker, John, 1974- (Wilfrid Laurier University Press, 2013)
Covers the outbreak of war in July-August 1914, the German invasion of Belgium, the Battles of the Frontiers, and the pursuit to the Marne in early September 1914.